Simulation of Double Walled Pipe Impact to Crude Oil Flow in Subsea Pipeline System - Dhimas Permadi; Sutopo Purwono Fitri; Wolfgang Busse (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
Crude oil contains mixed of hydrocarbons, the most commonly found molecules are alkanes (paraffins), cycloalkanes (naphthenes), aromatic hydrocarbons, or more complicated chemicals. In the process of taking crude oil in subsea pipeline system with depth 1200 meters, the contents of crude oil like sulfur, paraffin, asphalt could deposit in the wall of the pipe because of the different temperature between crude oil and wall of the pipe. The deposition can make blockage to the pipe and cause crude oil flow to be slow or stop. In this bachelor thesis, will be design double walled pipe for Subsea pipeline system with depth 1200 meters and simulation double walled pipe to knowing the impact of double walled pipe to crude oil flow in Subsea with depth 1200 meters. Based on the simulation that has been done, using double walled pipe could stabilize the temperature between crude oil and wall of the pipe. It shows that the average of temperature decrease using double walled pipe is only 0.125 K for 12 meters. So, it could get the conclusion based on the simulation of double walled pipe that the impact to crude oil flow is there’s no blockage in the pipe and the crude oil flow will steady.